Innovation In Bomba Batik Design As Contemporary Clothing Of Central Silawesi - Sintia Bongkolu; Henny J. Poli’i; Steven Rogahang (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the innovation of Batik Bomba design as contemporary clothing representing the cultural identity of Central Sulawesi. Batik Bomba, with its distinctive motifs such as Sero Tangga, Bomba Mawar, and Taiganja, reflects deep local values of harmony, perseverance, and prosperity. This research aimed to explore how traditional batik designs could be revitalized through innovation, technology, and sustainability to create fashion products that are both modern and culturally meaningful. The study also sought to assess how these design transformations contribute to cultural preservation and creative economic empowerment within local communities. This study employed a qualitative descriptive method conducted at the Department of Fashion Design, Universitas Negeri Manado. Data were collected through observation, interviews, literature study, and documentation involving two participants—students originating from Central Sulawesi who have knowledge of traditional Batik Bomba motifs. Data were analyzed using the Miles and Huberman interactive model, including data reduction, display, and conclusion drawing. The findings revealed that integrating traditional Batik Bomba motifs with contemporary design techniques successfully produced innovative and marketable fashion concepts. The application of modern technology such as Computer-Aided Design (CAD) and digital printing allowed precision and creativity, while sustainable practices using natural dyes supported eco-friendly production. The study concludes that innovation in Batik Bombadesign effectively bridges traditional artistry with modern fashion trends. This approach not only preserves cultural heritage but also enhances the creative economy of Central Sulawesi. Future development should focus on expanding global marketing strategies and strengthening collaborations among artisans, designers, and cultural institutions.